Lecturer Development Strategy to Improve Capabilities at STMIK Kaputama Binjai Towards Excellent Accreditation - Enda Beatrix Middlen PA; Prihatin Lumbanraja; Nazaruddin (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2025)
Lecturers play a strategic role in education quality, research, and institutional accreditation. The capability of lecturers significantly impacts the quality of higher education institutions. Preliminary surveys indicate limitations at STMIK Kaputama Binjai regarding the number of permanent lecturers, academic qualifications, and academic positions. This research aims to identify and formulate lecturer development strategies by analyzing external and internal factors to enhance lecturers' capabilities at STMIK Kaputama Binjai towards achieving superior accreditation. The study employed qualitative methods, including interviews and literature reviews, to construct strategic recommendations. Results obtained Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) scores of 3.14, positioning the institution within quadrant one (Grow and Build), indicating an aggressive growth strategy. The principal recommended strategies include regular lecturer capability enhancement programs, increased literacy and expertise in artificial intelligence, and strategic collaboration with relevant stakeholders. These strategies aim to elevate STMIK Kaputama into a leading, professional, and adaptive educational institution aligned with technological advancements and industrial demands.